Response of nutrients in submergence-prone rainfed lowland rice ecosystem with different flood histories - Laik, Ranjan; Singh, Santosh K; Kumar, Vipin; BH, Kumara; ., Nidhi; Kumari, Anupama; Hussain, Md. Sajid; Choudhary, Hemchandra; Singh, Sudhanshu; Kumar, Virendar (ORYZA-An International Journal of Rice, 2019)
Site specific nutrient management approach was used to understand response of rice (variety Swarna Sub-1) yields to applied nutrients in soils with different flood histories of Bihar. Trials on nutrient omission plot technique (NOPT) were conducted in four sites for nitrogen, phosphorus, potassium and zinc with four replications at each site. Per cent response of yield as compared to nutrient omission plots ranged from 36.4 to 77.2%, 10.9 to 37.2%, 5.8 to 17.0% and 4.3 to 32.9% with addition of N, P, K and Zn respectively. Differences  in response of applied nutrients were found due to difference in submergence condition and soil-nutrient status. The variation in nitrogen use efficiency was from 24.1 to 37.9%, phosphorus use efficiency from 22.1 to 33.6%, potassium use efficiency from 65.5 to 71.8% and zinc use efficiency from 2.72 to 3.93%. It may be concluded that soil nutrient contributions and level of submergence affected nutrient use efficiency and crop yield response to applied nutrients.